MEANING COST CEREMONY MOME'ATI (BEAT) IN PUBLIC GORONTALO (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Study This aim for know the meaning of fee in the Mome'ati (beating) Ceremony on public Gorontalo use approach Phenomenology. custom mom'ati is Wrong One custom Which held when a Woman Already get hindrance (period). Research methods This use method study qualitative with with approach Phenomenology. Methods of data collection carried out with method interview, observation, and documentation. From the results of these studies indicate that There is four meaning cost Which contained in ceremony Mom'ati (beating) public Gorontalo namely: Gratitude, Blessing, Friendship Event, And sincerity. All of this is actually a form of accountability to God, to Humans and to Nature, and in fact this accountability ultimately leads to the form Innalilahi wa innailahi wa inna lilahirojiun